Optical Properties of Eu3+-Doped Y2O3 Nanotubes and Nanosheets Synthesized by Hydrothermal Method - Peifen Zhu; William Wang; Hongyang Zhu; Preston Vargas; August Bont (IEEE Photonics Journal)
Y2O3:Eu3+ nanomaterials were obtained using a low-cost, large-scale, solution-based hydrothermal method followed by a thermal annealing process. The morphology of the Y2O3 :Eu3+ nanomaterials can be controlled by tuning the aging time, aging temperature, and the pH values of the suspension. The optical properties of Y2O3:Eu3+ nanosheets and nanotubes were investigated with the goal of improving the material's functionalities. Synchrotron X-ray diffraction patterns, field emission scanning electron microscopy images, high-resolution transmission electron microscopy images, emission spectra, excitation spectra, and fluorescence decay curves were measured and compared. The results showed that a novel Eu3+ environment exists in Y2O3:Eu3+ nanosheets, which led to rapid decay of emission at 611 nm. The unique properties of Y2O3:Eu 3+ nanosheets could lead to potential applications in white light-emitting diodes (LEDs) based on GaAlN deep UV LEDs.